Gender Streaming in Vietnam - Chowdhury, Iffat (World Bank, Washington, DC, 2018)
We examine the gender wage gap in Vietnam and show that a non-trivial part of the gap is associated with occupational sorting. We consider three explanations for why occupational sorting emerges. First, we explore whether occupational sorting is driven by gender differences in preferences for non-monetary characteristics of the jobs. First, we explore whether occupational sorting is driven by gender differences in preferences for non-monetary characteristics of jobs and find that there are indeed differences between the genders in preferences for having a formal contract, insurance, paid leave and shorter hours, which may induce women to forego monetary compensation for these characteristics. Second, we check if occupational sorting among the adult labor force is driven by social norms about gender roles learned and internalized at an early age. To do so we check for evidence of sorting in the aspirations of 12-year-old children by simulating what the gender wage gap would be if boys and girls pursued the occupations they aspire to at 12. And third, for women with higher education, we check if occupational sorting occurs during the school to work transition - if women are less likely to find jobs within their field of study upon graduation. We do not find support for either the second or third hypotheses. Overall, our findings suggest that in Vietnam gender specific preferences for non-monetary job characteristics play a key role in emergence of occupational sorting.